Dziecko z wadą słuchu w procesie kształtowania głosu i mowy = Hearing impaired child in the process of forming voice and speech - Lis-Zaldivar, Anna (Zielona Góra: Instytut Pedagogiki. Wydział Pedagogiki, Psychologii i Socjologii. Uniwersytet Zielonogórski)
Normal hearing, correct anatomical structure and well functioning speech and respiratory organs as well as an efficient nervous system are essential (fundamental) in forming voice and speech. In case of early childhood hearing impairment, phonetic-articulation distortions are likely to occur, leading to verbal communication disorders.
Keywords: dziecko; głos; mowa; utrata słuchu; wada słuchu; trening słuchowy; child; voice; speech; hearing loss; hearing impairment; auditory training